Effects of Inorganic and Organic Pollutants on the Biomarkers' Response of Cerastoderma edule under Temperature Scenarios - Mesquita, Andreia F (2023)
Currently, there is increased chemical pollution, and climate change is a major concern to scientific, political and social communities globally. Marine systems are very susceptible to changes, and considering the ecological and economic roles of bivalve species, like Cerastoderma edule, studies evaluating the effects of both stressors are of great importance. This study intends to (a) determine the toxicity of copper (Cu) and oxyfluorfen at the lethal level, considering the temperature; (b) assess the changes in the antioxidant defence enzymes as a consequence of the simultaneous exposure to chemical and warming pressures; and (c) determine if lipid peroxidation (LPO) and neurotoxic effects occur after the exposure to chemical and temperature stressors. C. edule was exposed to Cu and oxyfluorfen at different temperatures (15 °C, 20 °C and 25 °C) for 96 h. The ecotoxicological results reveal a higher tolerance of C. edule to oxyfluorfen than to Cu, regardless of the temperature. The antioxidant defence system revealed efficiency in fighting the chemicals' action, with no significant changes in the thiobarbituric reactive species (TBARS) levels to 15 °C and 20 °C. However, a significant inhibition of acetylcholinesterase (AChE) was observed on the organisms exposed to oxyfluorfen at 20 °C, as well as a decreasing trend on the ones exposed to Cu at this temperature. Moreover, the catalase (CAT) showed a significant increase in the organisms exposed to the two highest concentrations of Cu at 15 °C and in the ones exposed to the highest concentration of oxyfluorfen at 20 °C. Looking at the temperature as a single stressor, the organisms exposed to 25 °C revealed a significant increase in the TBARS level, suggesting potential LPO and explaining the great mortality at this condition.